Analysis of Vegetation Diversity and Emission Absorption Sufficiency on the Pandaan-Malang Green Toll Road - Izatullilah; Nurita Prameswari, Putri; Ahmad Abdul Aziz, Hafif; Ayu Kusuma Dewi, Vita (Jurnal Teknik Sipil dan Perencanaan, 2025)
Green corridors on toll roads are a natural strategy designed to reduce transportation emissions while maintaining the ecological function of the area. This study aims to assess the ability of vegetation to absorb carbon along the Pandaan–Malang Green Toll Road by comparing the total emissions produced by passing vehicles. The method employed is a quantitative descriptive approach with a bottom-up methodology to calculate carbon emissions and estimate CO₂ absorption, utilizing existing vegetation data. The research data revealed that the total annual emissions reached 63.32 million kg, while the total vegetation absorption was only 51.08 million kg or 19.33%, resulting in a deficit of 12.24 million kg (80.67%). Trembesi trees dominate, contributing around 90% of the total absorption, but dependence on this monoculture poses ecological risks due to pest attacks and climate pressure. Therefore, a species diversification strategy that focuses on zoning and strengthening technical regulations on green belts is needed. The policy implications aim to transform green highways from aesthetic elements into sustainable ecological infrastructure that actively functions in climate change mitigation and improves ecosystem service quality.